Tradition: a critical primer - Engler, Steven (Concepts in the study of religion, 2024)
"This book looks at the concept of tradition in the study of religion. It examines the history of the concept, uses in the discipline, theoretical perspectives (including Indigenous and post/decolonial studies, cognitive science and hermeneutics), and critical perspectives on key thinkers (Halbwachs, Gadamer, Ricoeur, J & A Assmann, Boyer, Morin) and recommendations for clearing the air of a key theoretical tension surrounding the concept of the invention of tradition"--